Trends in Apical Suspension at the Time of Hysterectomy for Pelvic Organ Prolapse: Impact of American College of Obstetricians and Gynecologists Recommendations. Issue 3 (March 2022) - Romanova, Anna; Sifri, Yara; Gaigbe-Togbe, Bertille; Hardart, Anne; Dabney, Lisa
Abstract : Objective: The aim of the study was to compare national surgical practice patterns of performing apical suspension procedures (ASPs) at the time of hysterectomy for pelvic organ prolapse (POP) before and after the publication of the American College of Obstetricians and Gynecologists (ACOG) 2017 Practice Bulletin on POP. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried for hysterectomy cases performed for POP indications for the years 2015–2016 and 2018–2019. The primary outcome was the use of ASP at the time of hysterectomy for POP. Secondary outcomes included the use of anterior, posterior, and paravaginal prolapse repair procedures. Multivariable regression analysis was performed to identify factors associated with performing a hysterectomy without an ASP. Results: A total of 11, 336 cases were included, and apical prolapse was the primary POP diagnosis in 86.3% of these cases. There was no statistically significant change in the utilization of ASPs in 2018–2019 compared with 2015–2016 (51.4% vs 49.8%, P = 0.081). Urogynecologists were significantly more likely than general gynecologists to perform ASPs (65.6% vs 37.5%, P < 0.001), which was confirmed on multivariable logistic regression analysis (adjusted odds ratio, 3.257; P < 0.001). The use of concomitant anterior repairs (44.1% vs 39.5%, P < 0.001) and posterior repairs (47.5% vs 41.3%, P < 0.001) increased in the 2018–2019 cohort. Conclusions: There was no overall increase in the utilization of concomitant ASPs at the time of hysterectomy done for POP indications despite the 2017 American College of Obstetricians and Gynecologists practice bulletin. Urogynecologists were more likely to perform ASPs than general gynecologists.